Management of pharmaceutical services in the Brazilian primary health care - Gerlack, Letícia Farias; Karnikowski, Margô Gomes de Oliveira; Areda, Camila Alves; Galato, Dayani; Oliveira, Aline Gomes de; Álvares, Juliana; Leite, Silvana Nair; Costa, Ediná Alves; Guibu, Ione Aquemi; Soeiro, Orlando Mario; Costa, Karen Sarmento; Guerra Junior, Augusto Afonso; et al. (Revista de Saúde Pública, 2017)
OBJECTIVE: To identify limiting factors in the management of pharmaceutical services in the primary health care provided by the Brazilian Unified Health System (SUS). METHODS: This study was based on the data from the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos no Brasil (PNAUM – National Survey on Access, Use and Promotion of Rational Use of Medicines), and it was conducted by interviews with professionals responsible for pharmaceutical services in Brazilian cities, in 2015. To identify the management limiting factors, we considered the organizational, operational, and sustainability indicators of the management. For the analyses, we included the weights and structure of analysis plan for complex samples. The results were expressed by frequencies and measures of central tendency with 95% confidence interval, considering the Brazilian geographic regions. RESULTS: We identified the following limiting factors: lack of pharmaceutical services in the Municipal Health Secretariat organization chart (24%) and in the health plan (18%); lack of participation of managers in the Health Board and the absence of reference to this topic in the agenda of meetings (58.4%); lack of financial autonomy (61.5%) and lack of knowledge on the available values (81.7%); lack of adoption of operational procedures (about 50%) for selection, scheduling, and acquisition; and the fact that most professionals evaluate the organization of pharmaceutical services as good and great (58.8%), despite the worrisome indicators. CONCLUSIONS: Pharmaceutical services management is currently supported by a legal and political framework that should guide and contribute to improve the pharmaceutical services in the Brazilian Unified Health System primary health care. However, there is a mismatch between the goals established by these guidelines and what is actually happening